2007
DOI: 10.1016/j.jconrel.2007.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Polymer platforms for drug delivery and biomedical imaging

Abstract: Biocompatible synthetic polymers have demonstrated advantageous pharmacokinetic properties as compared to small molecular agents. Incorporation of low molecular weight therapeutics and imaging agents into biocompatible polymers can optimize their pharmacokinetic properties with improved efficacy of therapy and diagnostic imaging, respectively. We have applied the concept of drug delivery to design safe and effective contrast agents for magnetic resonance imaging (MRI) and used biomedical imaging in non-invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…It was demonstrated that platforms to deliver only singlet oxygen, while conserving the embedded photosensitizer, may be synthesized [88]. Moreover, nanocarriers can contain not only photosensitizers particles, but also MRI contrast agents [89]. Optimal time of drugs systematic circulation can be ensured by modifying nanoparticles size (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that platforms to deliver only singlet oxygen, while conserving the embedded photosensitizer, may be synthesized [88]. Moreover, nanocarriers can contain not only photosensitizers particles, but also MRI contrast agents [89]. Optimal time of drugs systematic circulation can be ensured by modifying nanoparticles size (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These high density surface groups can be conjugated to drug molecules, targeting moieties and imaging agents, rendering dendrimers a versatile drug delivery platform. Surface groups on dendrimers can be modified to modulate cytotoxicity and permeation across biological barriers [100][101][102][103][104][105].…”
Section: Dendrimersmentioning
confidence: 99%
“…These agents were anticipated to be beneficial for the accumulation of MRI labels at regions of interest and allowed bimodality in imaging, thereby integrating the advantages of different imaging techniques [86][87][88]. Therefore, dendrimers were uniquely qualified to establish this site-specific system as the carriers with large numbers of reactive functional groups on the surface [89][90][91].…”
Section: Organic or Tissue-targeting Dendritic Mri Contrast Agentsmentioning
confidence: 99%
“…Other carbohydrate-functionalized dendritic agents with a bivalent fluorescent label and dendrimers with multiple gadolinium chelates and multiple oligopeptides for targeting were reported. Dendritic target-specific MRI contrast agents based on a biotinylated oligopeptide equipped with Gd(III)DTPA and avidin, and dendritic contrast agents composed of Gd(III)DTPA and oligopeptides were studied previously ( Figure 4) [87,[98][99][100][101].…”
Section: Organic or Tissue-targeting Dendritic Mri Contrast Agentsmentioning
confidence: 99%
See 1 more Smart Citation